Arthropod responses to potential disturbances, patch conditions and landscape composition in South African Southern Mistbelt Forests - Nel, Abbygale (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScConEcol)--Stellenbosch University, 2026.